2y+26-8y=5

Simple and best practice solution for 2y+26-8y=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+26-8y=5 equation:


Simplifying
2y + 26 + -8y = 5

Reorder the terms:
26 + 2y + -8y = 5

Combine like terms: 2y + -8y = -6y
26 + -6y = 5

Solving
26 + -6y = 5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + -6y = 5 + -26

Combine like terms: 26 + -26 = 0
0 + -6y = 5 + -26
-6y = 5 + -26

Combine like terms: 5 + -26 = -21
-6y = -21

Divide each side by '-6'.
y = 3.5

Simplifying
y = 3.5

See similar equations:

| 4m-3n=3 | | X(y)=38.25 | | 2500+150n=3000+125n | | -5(3-h)+4=5h-11 | | -7+6x=17+8x | | 7w+3=3w+94 | | 4m+3n=69 | | -7(-2x-7)+8x=-31+2x | | 3+7=2x+3 | | -8*-7+9*-7-21=-12-16 | | 5t-13=9+5t | | 2(5-2h)=20-2(h-1) | | 2a+2a=bc | | 5d-9-(7-4d)= | | (-5)+(7.1)= | | -4(4+6)=-63 | | -5-4y=39 | | 1-6x=73 | | 5-x-3=10 | | 3s-4=3(s-1) | | 12x+-2=70 | | 3x+-11=x+-11 | | 4(8x-28)=80 | | 3=t+5s | | 40(t+0.5)=80 | | (9+h)=20 | | 2fg(3fg^2h*5f^3h^2)= | | 7r-6=10-r | | 2g^2+g-10=0 | | x^2+13x+9=4x+1 | | 6-3(2v+2)=4(8-v) | | 49p^3q-64pq^3= |

Equations solver categories